Reviews: Talent identification in soccer: The role of maturity status on physical, physiological and technical characteristics - Meylan, C.; Cronin, J.; Oliver, J.; Hughes, M. (International Journal of Sports Science and Coaching, 2011)
The purpose of this paper is to provide a review around talent identification in soccer using physiological and technical testing procedures, and to summarise the issues associated with this process. The current research in soccer talent identification, among other sports, demonstrates a systematic bias in selection towards players born early in the year (i.e., relative age effect) and early maturers. From the studies investigating the physiological (e.g., power) and technical (e.g., dribbling) characteristics of players of different maturity status, early maturers had the tendency to perform better in these tests and therefore were likely to be more influential on the game and be recognised as more talented. When considering the current level of play and future success, elite youth and future professional players scored better in physiological and technical testing than recreational youth and future non-professional players, independently of maturity status. However, these testing procedures were not sensitive enough to distinguish youth elite from sub-elite or future national team from professional club players. Collectively, these studies demonstrated the need to use estimates of maturity status and subsequent appropriate analysis of data obtained from physiological and technical testing. When maturity is taken into account, these testing procedures can provide an indication of responsiveness to training load in youth players and an evaluation of potential to become a successful soccer player. However, these testing procedures should not be used as a marker of selection before full maturity is attainted and should be part of a multidimensional approach of talent identification considering the importance of other facets of the game at the highest level (e.g., perceptive-cognitive skills).